REINTERPRETASI PEMBAGIAN HARTA WARISAN MENURUT MUHAMMAD SYAHRUR: ANALISIS ATAS Q.S. AN-NISA AYAT:11 - Nur Shofi'i, Eri (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study aims to examine the construction of inheritance flexibility according to Syaḥrūr, identify the underlying assumptions that shape his divergent interpretation, and analyze its implications for classical exegetical frameworks. Employing Karl Mannheim’s sociology of knowledge, the study finds that Syaḥrūr views inheritance verses as establishing minimum and maximum limits, allowing women’s shares to approach those of men depending on economic contribution and socio-historical contexts. Second, his approach is grounded in the concept of ṡubūt an-naṣ wa taghayyur al-muhtawā, which posits that the Qur’anic text is fixed while its meanings may evolve. Third, through his ḥudūd theory, Syaḥrūr enacts a significant paradigm shift by rejecting the classical notion of qaṭ’iyyah ad-dilālah, thereby reopening the space for ijtihad in Islamic inheritance law.